Effect of natural filler on the characterization of natural rubber - Kamarah, Santini Raj (2010)
In this paper the effect of natural filler on the characterization of natural rubber will be investigated. Usage of natural rubber only to produce rubber products becomes disadvantages in economical and environmental aspect. It will be more efficient if the rubber is reinforced with filler as its additive without affecting its properties. Moreover, the increase interest in using natural fillers as reinforcement in natural rubber to substitute the conventional fillers has become one of the main concerns in nowadays. For this study natural rubber that been used is Standard Malaysian Rubber (SMR) while coconut fiber is the natural filler that being use to reinforced the SMR. The composite material using natural rubber and coconut filler are being done in two methods; first method is by mixing by using two roll mills to the natural rubber without any additional of fillers. The second method is to mix homogeneously the natural rubber with different loading (0-50phr) of coconut fiber. Later chemical substances such as sulphur, softener, accelerator and etc were added using rolling process according to the formulation. The cured rubber is molded using hot press and sample is cut manually from the molded rubber for the testings. As the filler loading increases, the time consumed to blend the SMR and filler are getting long because the volume of coconut fiber is increasing. The mixing or rubber and other additive are also getting tougher as the filler loading increasing. The tensile strength is decreasing as the filler loading increases. Besides that, extension at break and time at break is decreasing when the filler loading is increasing. For swelling test, kerosene diffuse more than diesel in the reinforced rubber but decreasing as the filler loading increases. It is concluded that the new composite material using natural rubber and coconut filler giving less strength than using conventional filler. In conjunction of that, using of natural filler as reinforced for rubber is best for the products that need less strength.